Diverse representation in Frontotemporal Dementia research studies: implications for clinical trials. (20th December 2022) - Piña‐Escudero, Stefanie Danielle; Franco, Teresita Ramos; Slachevsky, Andrea; Yokoyama, Jennifer S.
Abstract: Background: The Multi‐Partner Consortium to Expand Dementia Research in Latin America (RedLat) study is a niche for the implementation of clinical trials on Frontotemporal Dementia in Latin America. We identified that one of the main limitations of recruitment was a lack of clinicians with comprehensive knowledge on Frontotemporal Dementia in the region. We aimed to fill these gaps by creating an online training for physicians. Method: A group of American and Latin American brain health experts trained at the Global Brain Health Institute at the University of San Francisco California is delivering an abridged online behavioral neurology training project to a pilot group of 30 neurologists, geriatricians, and psychiatrists from Latin America. The training highlights important aspects such as culturally appropriate neuropsychological assessment and functional assessment to adequately classify participants under the frontotemporal dementia umbrella. A component about the importance of research including clinical trials is also being delivered. Baseline evaluations about the quality of their medical training regarding dementia and a dementia knowledge evaluation were conducted and we are expecting to conduct an evaluation in the third and sixth months. Result: On the baseline evaluation, 80% classified the information they received as "poor", 12% classified the information as "sufficient" and 8% classified it as "good". Regarding baseline dementia knowledge, the mean score was 5.2 (SD ± 2.5) out of a maximum score of 10 points. We expect an increase in these numbers during the upcoming evaluations. As a side outcome, participants from this project are building pipelines to increase recruitment in RedLat. Conclusion: Overcoming existing educational barriers of diagnosis of Frontotemporal Dementia as well as generating awareness of the importance of clinical trials in Latin America will hopefully be a key tool to increase the representation of persons with Frontotemporal Dementia. We will discuss the importance of adequate diagnosis and classification of frontotemporal dementia by the professionals who serve these underrepresented populations and the importance that this first step has to adequate recruitment into clinical trials.